2011
DOI: 10.1111/j.1466-8238.2010.00628.x
|View full text |Cite
|
Sign up to set email alerts
|

Biogeographical patterns of soil molecular microbial biomass as influenced by soil characteristics and management

Abstract: Aim The spatial organization of soil microbial communities on large scales and the identification of environmental factors structuring their distribution have been little investigated. The overall objective of this study was to determine the spatial patterning of microbial biomass in soils over a wide extent and to rank the environmental filters most influencing this distribution.Location French territory using the French Soil Quality Monitoring Network. This network covers the entire French territory and soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
161
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 222 publications
(197 citation statements)
references
References 59 publications
24
161
1
2
Order By: Relevance
“…Recent microbial biogeography studies have revealed that the main environmental filters shaping spatial microbial diversity distribution are soil physico-chemical characteristics, land use and plant cover, whereas climatic and geomorphologic filters are less important 9,11,15,37 . Similar filters were also reported to explain soil bacterial community distribution in contrasted ecological regions at the scale of France 27,34 .…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Recent microbial biogeography studies have revealed that the main environmental filters shaping spatial microbial diversity distribution are soil physico-chemical characteristics, land use and plant cover, whereas climatic and geomorphologic filters are less important 9,11,15,37 . Similar filters were also reported to explain soil bacterial community distribution in contrasted ecological regions at the scale of France 27,34 .…”
Section: Discussionsupporting
confidence: 77%
“…In addition, DNA fingerprinting precludes consideration of the accumulation of new minor species ARTICLE with increasing distance, which may represent a large proportion of the total soil microbial species richness 33 and determine the slope of TAR 14,31 . The low z bacteria might also be related to the grain size of our sampling design (16 km  16 km: 256 km 2 ), which did not consider scales less than landscape, and smoothed significant local variations in soil microbial community composition that might potentially affect TAR 34 . In parallel, soil habitat was characterized by a multivariate analysis including pedoclimatic, geomorphologic and land-use data, and the HAR was calculated by transposing the TAR concept.…”
Section: Discussionmentioning
confidence: 99%
“…Wakelin et al (2008) found that soil pH was the dominant driver of microbial community structure and function in a range of Australian agricultural soils. Despite the large number of studies focusing on the driving factors of microbial distribution under a specific environmental gradient at regional or local scale, studies of microbial biogeography at large spatial scales have only been initiated recently (Fierer and Jackson, 2006;Drenovsky et al, 2010;Griffiths et al, 2011;Dequiedt et al, 2011). A notable example was the investigation of bacterial biogeography in British soil (Griffiths et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies on soil MB have been conducted in the past few decades (Dempster et al, 2012;Kaschuk et al, 2010;Xu et al, 2013), and the focus has recently changed from site/ecosystem level Wright and Coleman, 2000;Zak et al, 1994) to regional (Dequiedt et al, 2011;Drenovsky et al, 2010) and global scales (Serna-Chavez et al, 2013;Xu et al, 2013). These large-scale studies examined microbial biomass storage and the mechanisms determining its spatial patterns.…”
Section: Introductionmentioning
confidence: 99%